High-Temperature Stealth Across Multi-Infrared and Microwave Bands with Efficient Radiative Thermal Management - Zhao, Meng; Zhu, Huanzheng; Qin, Bing; Zhu, Rongxuan; Zhang, Jihao; Ghosh, Pintu; Wang, Zuojia; Qiu, Min; Li, Qiang (Nano-Micro Letters, 2025)
High-temperature stealth is vital for enhancing the concealment, survivability, and longevity of critical assets. However, achieving stealth across multiple infrared bands—particularly in the short-wave infrared (SWIR) band—along with microwave stealth and efficient thermal management at high temperatures, remains a significant challenge. Here, we propose a strategy that integrates an IR-selective emitter (Mo/Si multilayer films) and a microwave metasurface (TiB2–Al2O3–TiB2) to enable multi-infrared band stealth, encompassing mid-wave infrared (MWIR), long-wave infrared (LWIR), and SWIR bands, and microwave (X-band) stealth at 700 °C, with simultaneous radiative cooling in non-atmospheric window (5–8 μm). At 700 °C, the device exhibits low emissivity of 0.38/0.44/0.60 in the MWIR/LWIR/SWIR bands, reflection loss below − 3 dB in the X-band (9.6–12 GHz), and high emissivity of 0.82 in 5–8 μm range—corresponding to a cooling power of 9.57 kW m−2. Moreover, under an input power of 17.3 kW m−2—equivalent to the aerodynamic heating at Mach 2.2—the device demonstrates a temperature reduction of 72.4 °C compared to a conventional low-emissivity molybdenum surface at high temperatures. This work provides comprehensive guidance on high-temperature stealth design, with far-reaching implications for multispectral information processing and thermal management in extreme high-temperature environments. Highlights: 1 Simultaneous stealth across multiple infrared bands (short-wave infrared (SWIR), mid-wave infrared (MWIR), long-wave infrared (LWIR)) and microwaves at high temperatures (700 °C) is achieved. 2 At 700 °C, the device features low emissivity of 0.38/0.44/0.60 in MWIR/LWIR/SWIR bands, reflection loss below − 3 dB in the X-band (9.6–12 GHz), and high emissivity of 0.82 in the 5–8 μm range. 3 Under an input power equivalent to Mach 2.2 aerodynamic heating, effective thermal management achieves a 72.4 °C temperature reduction compared to conventional low-emissivity molybdenum.